Ectopic expression of a tobacco vacuolar invertase inhibitor in guard cells confers drought tolerance in Arabidopsis. (1st November 2016) - Chen, Su-Fen; Liang, Ke; Yin, Dong-Mei; Ni, Di-An; Zhang, Zhi-Guo; Ruan, Yong-Ling
Abstract: There are several hypotheses that explain stomatal behavior. These include the concept of osmoregulation mediated by potassium and its counterions malate and chlorine and the more recent starch–sugar hypothesis. We have previously reported that the activity of the sucrose cleavage enzyme, vacuolar invertase (VIN), is significantly higher in guard cells than in other leaf epidermal cells and its activity is correlated with stomatal aperture. Here, we examined whether VIN indeed controls stomatal movement under normal and drought conditions by transforming Arabidopsis with a tobacco vacuolar invertase inhibitor homolog ( Nt-inhh ) under the control of an abscisic acid-sensitive and guard cell-specific promoter ( AtRab18 ). The data obtained showed that guard cells of transgenic Arabidopsis plants had lower VIN activity, stomatal aperture and conductance than that of wild-type plants. Moreover, the transgenic plants also displayed higher drought tolerance than wild-type plants. The data indicate that VIN is a promising target for manipulating stomatal function to increase drought tolerance.